2024
DOI: 10.1002/adma.202307913
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Electrocatalytic Hydrogenation Reactions on Copper‐Based Catalysts

Min Zheng,
Junyu Zhang,
Pengtang Wang
et al.

Abstract: Hydrogenation reactions play a critical role in the synthesis of value‐added products within the chemical industry. Electrocatalytic hydrogenation (ECH) using water as the hydrogen source has emerged as an alternative to conventional thermocatalytic processes for sustainable and decentralized chemical synthesis under mild conditions. Among various ECH catalysts, copper‐based (Cu‐based) nanomaterials are promising candidates due to their earth‐abundance, unique electronic structure, versatility, and high activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 283 publications
0
0
0
Order By: Relevance
“… 64 Electrochemical impedance spectroscopy (EIS) at different potentials (0.05, 0.1, 0.15, and 0.25 V vs Ag/AgCl) showed reduced charge transfer resistance in CNGO/ZnSe compared to CNGO, indicating improved charge transfer, which we attribute to the spatial separation of excited charge carriers across the heterojunction as a result of the type–II band alignment ( Figure S7 ). 65 , 66 Chronopotentiometric open circuit potential ( V OC ) measurements for CNGO and CNGO/ZnSe films further examine the quasi-equilibrium attained in the dark or under illumination, where generation, accumulation, and recombination of photoinduced electron–hole pairs take place. Compared to a CNGO film alone, the CNGO/ZnSe composite photoanode exhibits a more negative V OC under 1 sun illumination ( Figure S8 ), suggesting that the presence of ZnSe NCs facilitates the accumulation of photoinduced electrons within the CB of CNGO, thereby promoting the separation of excitons.…”
Section: Resultsmentioning
confidence: 99%
“… 64 Electrochemical impedance spectroscopy (EIS) at different potentials (0.05, 0.1, 0.15, and 0.25 V vs Ag/AgCl) showed reduced charge transfer resistance in CNGO/ZnSe compared to CNGO, indicating improved charge transfer, which we attribute to the spatial separation of excited charge carriers across the heterojunction as a result of the type–II band alignment ( Figure S7 ). 65 , 66 Chronopotentiometric open circuit potential ( V OC ) measurements for CNGO and CNGO/ZnSe films further examine the quasi-equilibrium attained in the dark or under illumination, where generation, accumulation, and recombination of photoinduced electron–hole pairs take place. Compared to a CNGO film alone, the CNGO/ZnSe composite photoanode exhibits a more negative V OC under 1 sun illumination ( Figure S8 ), suggesting that the presence of ZnSe NCs facilitates the accumulation of photoinduced electrons within the CB of CNGO, thereby promoting the separation of excitons.…”
Section: Resultsmentioning
confidence: 99%
“…Within this context, extensive research revealed the effect of the intrinsic properties of catalytic materials for guiding the design of highly efficient catalysts. 17,18 Meanwhile, the influence of other parameters, such as the pH of the electrolyte, 16,19,20 applied potential 21,22 and reactant concentration, 23–25 has also been investigated. Kwon et al reviewed the effect of electrode materials, 26 and Biddinger's group also highlighted the strategies to obtain target products and inhibit competing reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Selective semi-hydrogenation of alkynes into alkenes is an important catalytic reaction for the synthesis of value-added fine chemicals 1 3 . Currently, the semi-hydrogenation reaction of alkynes is commonly operated (thermo)chemical hydrogenation (TCH), where the flammable and explosive H 2 gas as the source is catalytically dissociated for subsequent hydrogenation of alkynes under high temperature and pressure conditions 4 6 .…”
Section: Introductionmentioning
confidence: 99%